Religious missionary life abroad and English-speaking motivation among Canossian Sisters: A phenomenological study - Natalina Antónia dos Santos; Concilianus Laos Mbato (Journal on English as a Foreign Language, 2026)
While there is considerable research on the motivation to learn and speak English among students and teachers, there is little research on the motivation to speak English among religious women living in another country. This study aimed to investigate the lived experiences of four Timorese Canossian Sisters, three of whom are currently living in the Philippines, and one lived there years ago. A phenomenological design was employed to capture the lived experiences of the participants and to understand how they navigated their new environment relating to language, culture, and mission. Data were collected through self-reflective narratives and focus group discussions, and were analysed thematically. The findings show that participants’ motivation to speak English evolved from obligation and compliance to intrinsic and integrative motivation, which in turn helped them overcome personal insecurities such as language anxiety and shyness. Community encouragement, cultural adaptation, religious missions, self-belief, and peer support contributed to this change. This research implies creating an environment that supports religious communities, identifies sensitive practices, and mediates social learning to increase learners’ speaking motivation in various cultural and faith-based contexts. It contributes to the literature on second language motivation in relation to religious life and transnationalism.